A novel ribozyme-based prophylaxis inhibits influenza A virus replication and protects from severe disease. - Julie Motard; Ronan Rouxel; Alexandra Paun; Veronika von Messling; Martin Bisaillon; Jean-Pierre Perreault (PLoS ONE)
Influenza A virus seasonal outbreaks and occasional pandemics represent a global health threat. The high genetic instability of this virus permits rapid escape from the host immune system and emergence of resistance to antivirals. There is thus an urgent need to develop novel approaches for efficient treatment of newly emerging strains. Based on a sequence alignment of representatives from every subtype known to infect humans, we identified nucleic acid regions that are conserved amongst these influenza A populations. We then engineered SOFA-HDV-Ribozymes as therapeutic tools recognizing these conserved regions to catalytically cleave the corresponding viral mRNA targets. The most promising ribozymes were chosen based on an initial in silico screening, and their efficacy was assessed using in vitro cleavage assays. Further characterization of their antiviral effect in cell culture and in mice led to the gradual identification of prophylactic SOFA-HDV-Ribozyme combinations, providing proof-of-principle for the potential of this novel strategy to develop antivirals against genetically highly variable viruses.